Perancangan Aplikasi E-Commerce Berbasis Website Menggunakan Algoritma Content Based-Filtering Pada Toko Smoodie Foodie - Arifin, Muhammad Khoirul; Mugiarso; Sari, Rafika (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
The development of digital technology is driving transformation in the trade sector, including the increasing use of e-Commerce platforms. However, challenges such as sales disparities between products still occur, such as at the Smoodie Foodie Store, which still operates conventionally, where 5 of its 16 products have a low sales conversion rate despite being promoted. This research aims to design an e-Commerce system that facilitates online purchases and increases the visibility of less popular products through the Content-Based Filtering (CBF) algorithm. The system development uses the Waterfall method, from analysis to testing. The uniqueness of this research lies in the integration of a recommendation feature that displays similar products based on title attributes. The result is an e-Commerce application that is able to recommend products effectively and increase the visibility of products with low sales. Next, system testing covered key functions such as registration, login, product and order management by the admin, and adding products to the cart by the user. Based on the test results, all features showed a